1993
DOI: 10.1111/j.1476-5381.1993.tb13531.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the endothelium in the response to cholinoceptor stimulation of rabbit ear and femoral arteries during cooling

Abstract: 1 The role of the endothelium in the effects of cooling on the response to cholinoceptor stimulation of the rabbit central ear (cutaneous) and femoral (non-cutaneous) arteries was studied using 2 mm long cylindrical segments.2 Concentration-response curves for acetylcholine (I0-9-IO-OM), methacholine (10-9-1iO-M) and sodium nitroprusside (IO-9-IO-4M) were isometrically recorded in arteries under conditions, with and without endothelium or following pretreatment with the nitric oxide-synthesis inhibitor N0-nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
33
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 24 publications
11
33
3
Order By: Relevance
“…Treatment with L-NAME also increased the sensitivity to phenylephrine at 28°C, suggesting that the production of NO in the endothelium can be increased under moderate hypothermia. Thus, the response of the spermatic vein to moderate hypothermia in this study is in agreement with that of the cutaneous vessels of different species (9,17). The reason for this discrepancy may be related to differences between arteries and veins, skin vascular regions, and perhaps species.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Treatment with L-NAME also increased the sensitivity to phenylephrine at 28°C, suggesting that the production of NO in the endothelium can be increased under moderate hypothermia. Thus, the response of the spermatic vein to moderate hypothermia in this study is in agreement with that of the cutaneous vessels of different species (9,17). The reason for this discrepancy may be related to differences between arteries and veins, skin vascular regions, and perhaps species.…”
Section: Discussionsupporting
confidence: 76%
“…It has vasodilator activity and its local level is controlled by biosynthesis from the inactive precursor L-arginine. As vascular relaxants, the endothelium can produce NO from L-arginine (9).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that the relaxation to cholinergic stimulation of ear artery, but not of femoral artery, from rabbit was increased during cooling. 28) Theˆnd-ings in guinea-pig myocardium and aorta support our results; Saito et al 4) reported that the vasorelaxant eŠects of K + channel openers, NIP-121, cromakalim, and pinacidil, were greatly reduced during cooling. However, the mechanism underlying the eŠect of cooling to diŠerent agents is not clear.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, Bodellson et al 31) reported that cooling speciˆcally alters the sensitivity to various drugs in diŠerent parts of the vascular systems; in the rat jugular vein, cooling markedly augments the contraction to 5-HT and it has been found that this augmentation is dependent of an intact endothelium. Monge et al 28) reported that the relaxations of ear arteries, but not of femoral arteries, from rabbits to cholinergic stimulation is increased during cooling, probably by an increased production of nitric oxide in the activated endothelium at low temperature. It is also reported that the increased sensitivity of the relaxation in ear arteries, but not in femoral arteries, to histamine found during cooling seems to be independent of the release of nitric oxide.…”
Section: Discussionmentioning
confidence: 99%
“…The endothelium can produce nitric oxide from L-arginine which causes vascular relaxation (Palmer et al, 1988). In addition to agonist-mediated constriction, limited evidence suggests that vascular smooth muscle responsiveness to nitric oxide and related factors can be influenced by temperature (Karaki and Nagase, 1987;Monge et al, 1993;Garcia-Villalon et al, 1995). Recently, we studied the effects of temperature on the contractile responses of smooth muscle preparations in a variety of vessels from different species and observed that the contractile responses were temperature-dependent, with the endothelium appearing to have no role in these responses (Atalik et al, 2000;Atalik et al, 2001a;Atalik et al, 2003).…”
Section: +mentioning
confidence: 99%